The interaction of post-activation potentiation and fatigue on skeletal muscle twitch torque and displacement - Langen, Georg; Warschun, Frank; Ueberschär, Olaf; Behringer, Michael (Frontiers in Physiology, 2025)
IntroductionTensiomyography (TMG) assesses skeletal muscle contractile properties based on the electrically stimulated radial muscle displacement. As the relationship between twitch displacement and associated torque is poorly understood, it is unclear how it is affected by post-activation potentiation and muscle fatigue. This study investigated how the interaction of potentiation and fatigue affects the rectus femoris (RF) twitch displacement and associated torque.Materials and methodsSixteen resistance-trained men (n = 8) and women (n = 8) performed two sets of five and five sets of ten seated maximum voluntary isometric knee extensions to induce potentiation and fatigue. Twitch displacement and torque were measured at baseline before the first set, after each set, and every 2 min for 15 min after the last set.ResultsThe exercise effectively induced potentiation and fatigue as peak twitch torque increased by 44.1% after the first set, decreased by 32.9% after the last set and remained decreased by 26.4% after 15 min. Twitch displacement was considerably less affected by the exercise. Consequently, TMG parameters could not accurately detect potentiated or fatigued participants as indicated by the peak twitch torque.DiscussionThe TMG parameters’ insufficient diagnostic accuracy likely resulted from a reduced signal-to-noise ratio at 90° knee flexion and the associated longer muscle length of the RF, compared to more extended knee angles commonly employed in TMG studies. These results highlight an important methodological consideration as the joint angle, i.e. muscle length, appears to influence the TMG parameters’ ability to detect exercise-induced changes in contractile properties.